Managing Home Oxygen and Nasogastric Feeds Post-NICU Discharge: PCP Practices and Perspectives - Beard, Lauren A.; Weikel, Blair W.; Hannan, Kathleen E.; Messinger, Amanda I.; Bourque, Stephanie L. (American Journal of Perinatology, 2025)
NICU graduates are frequently technology dependent including home oxygen, pulse oximetry, and/or nasogastric (NG) feedings. Primary care provider (PCP) perceptions, practices, and barriers to managing these infants are not well described, especially at altitude. We sought to 1) describe PCP comfort and 2) determine practices and barriers in managing this technology at higher altitudes.This cross-sectional survey assessed Colorado and Wyoming PCP perceptions and practices surrounding technology in NICU graduates. We explored bivariate analysis between clinic altitude, location, and provider's experience with comfort caring for infants discharged with technology using chi-squared or Fisher's exact tests. Significant relationships were modeled using logistic regression for odds ratios and 95% confidence intervals.Among 203 respondents, 82% were pediatricians, and 86% practiced in urban/suburban environments. Clinic altitude ranged 2,500–9,000 ft. PCPs endorsed comfort managing oxygen in term (92%) and moderately/late preterm infants (82%), versus 52% comfort in very/extremely preterm infants. 62% utilized an oxygen-weaning algorithm. Comfort managing oxygen was greater in suburban versus urban locations (odds ratio [OR] = 4.4, 95% confidence interval [CI]: 1.6–11.7) and providers practicing for >10 versus <5 years (OR = 3.5, 95% CI: 1.5, 8.4). 60% found pulse oximetry useful, though 70% perceived caregiver stress. 69% accepted infants on NG feeds, though 61% endorsed discomfort with management.PCPs are comfortable managing home oxygen in moderately preterm to term infants but find caring for most preterm infants challenging. Discomfort in managing NG feeds is prevalent. This highlights peridischarge barriers and improvement opportunities for high-risk, technology-dependent infants.
Keywords: neonatology; NICU discharge; home oxygen therapy; feeding difficulties; home pulse oximetry